Pola Pembiayaan Syariah Murabahah Di Kota Bengkulu - Barika Barika; Ronicha Melsy (Universitas Bengkulu, 2021)
This research aims to determine the pattern of BMT sharia financing in Bengkulu City in terms of murabahah at three BMTs in Bengkulu City. The data used are sourced from chairman, manager, teller and financial department interviews at Bmt Bengkulu City and analyzed at using descriptive statistical analysis. The results of this study indicate that the most popular financing for members of BMT in Bengkulu City is the murabaha financing pattern with the composition of financing based on the amount of financing that is 85.30% and based on the number of recipients of financing that is equal to 86.50%.